PROSES PEMEKARAN KELURAHAN DI KOTA PEKANBARU TAHUN 2016-2017 - Alfajri Eko Setia; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The reason for the expansion of Kelurahan in the City of Pekanbaru is the ever increasing number of residents in each parent village. The increase in population also automatically increases the volume of activities in the fields of government, development, and society. Based on these considerations, the main kelurahan is considered to be ineffective and inefficient in providing services, such as the length of time for completion in administering an administrative service, slow development, and fostering community affairs that are becoming less focused, so that the pemekeran in a number of districts in Pekanbaru City is considered as one of the policies that can solve this problem..This research was conducted in the villages resulting from the division in Pekanbaru City. The informants in this study are those who are competent in the process of urban sprawl in the city of Pekanbaru such as the Commission I of the Pekanbaru City DPRD, Head of Governance, Camat, Lurah, kelurahan staff and community leaders. One of the factors to do the division of Kelurahan in Pekanbaru City is the increasing number of population in each main village. The results of this study indicate that the process of pemekaran is the desire of the community to bloom several villages in Pekanbaru in principle aimed at improving the welfare of the community. Keyword : Process, Kelurahan, Expansion